1995
DOI: 10.1111/j.1365-2044.1995.tb05942.x
|View full text |Cite
|
Sign up to set email alerts
|

Health and activity after intensive care

Abstract: SummaryAll patients discharged from a general intensive care unit over a 4.5year period were sent a questionnaire 3 months after discharge which investigated aspects of their health andphysical abilities. Replies were compared on the basis of age, diagnosis and sickness severity on admission. Five hundred and four questionnaires were analysed. Overall, 47% of patients described their health as goodlvery good, 42% as fair and I I % as poor/very poor. Activity level, compared to that before their admission, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Mortality after discharge from intensive care ranges from 9% to 27%. 18 19 Our discharge triage model used objective data (age, end stage disease, physiology, length of stay, and cardiac surgery) in a logistic regression equation to identify patients at risk from inappropriate early discharge. We were able to do this because the database of the Riyadh ICU program captures daily data throughout a patient's stay in intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality after discharge from intensive care ranges from 9% to 27%. 18 19 Our discharge triage model used objective data (age, end stage disease, physiology, length of stay, and cardiac surgery) in a logistic regression equation to identify patients at risk from inappropriate early discharge. We were able to do this because the database of the Riyadh ICU program captures daily data throughout a patient's stay in intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…Two considered patient age and found no statistically significant association. 155,278 Rowan 155 and Hurel and colleagues 237 also found no association with patient gender. Criterion validity was explored in four studies.…”
Section: Measurement Properties In Critical Carementioning
confidence: 97%
“…Eleven studies have reported on the NHP as an outcome measure in following-up critical care patients ( Table 71 ). 119,139,155,156,218,237,263,[277][278][279][280] One study used a simplified version of the NHP. The mean ages of the participants ranged from 23 years to 64 years and the percentages of male participants ranged from 49% to 68%.…”
Section: Application In Critical Carementioning
confidence: 99%
“…However, in one study, only 16.9 percent of patients under 61 years of age who were discharged from a general ICU were subsequently employed. 22 To estimate indirect costs, we multiplied this estimate of the employment rate (16.9 percent for patients younger than 60 years and 0 percent for patients 60 years of age or older) by the average gross annual salary of a full-time Canadian worker (33,384 Canadian dollars). 23…”
Section: Costs For the Conventional-care Cohortmentioning
confidence: 99%